Learning Science from the Local Environment: Integrating Ethnoscience-Based Local Knowledge into Elementary IPAS Learning - Saleha, Saleha; Nadar, Nadar; Masnur, Masnur (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Science and social science (IPAS) learning that is closely connected to students’ everyday lives can bridge community-based knowledge and scientific understanding in the classroom. This study aimed to identify local community knowledge, reconstruct it into scientific concepts, and analyze the integration of ethnoscience into IPAS learning among fifth-grade students at SD Negeri 53 Malalin, Enrekang Regency, Indonesia. The study employed a qualitative case study design involving 22 fifth-grade students, one classroom teacher, and three community informants. Data were collected through observations, semi-structured interviews, documentation, student activity sheets, and learning reflections. The findings identified four local food-processing practices: dangke, deppa tettekan, dangke chips, and baje. These practices could be reconstructed into relevant scientific concepts, including changes in material properties, heat transfer, evaporation, enzyme activity, protein coagulation, and the use of local resources. The integration of ethnoscience through observation, exploration, comparison, and reflection helped students move from experience-based knowledge toward more scientific explanations of familiar phenomena. These findings indicate that local knowledge can serve as a meaningful contextual learning resource that strengthens the connection between culture, everyday experience, and scientific thinking in IPAS learning.